Avoiding Unnecessary Exposure of User Profile in Web Search - Karanam, Madhavi (International Journal of Computer Sciences and Engineering, 2025)
While the amount of information on the web reliably develops, it offers come to be an expanding number of confused as to internet web indexes to find data that satisfy clients' specific individual needs. Modified hunt can be certain techniques to help seek through tweaking postings in the event that you have not at all like data desire. Decent customization criteria will rely on upon internet corpus and inexhaustible individual single profiles. Interestingly, for the reason that internet corpus is really resting for the server, re-positioning for the customer side is really transmission capacity engaged as it needs a colossal number associated with postings went to the customer sooner than re-positioning. Almost all individualized search products and functions on the web like bing, www and Google Customized Search put into act your second move toward to adjust effects for the server through analyzing collected confidential information, electron search histories and personalized interests. In this paper a technique named user preference hierarchy is proposed. Experimental results show that the proposed technique gives better results than existing technique such as personal web search.